Localized loading and nonlinear instability and post-instability of fixed arches. (October 2018) - Lu, Hanwen; Liu, Airong; Pi, Yong-Lin; Bradford, Mark Andrew; Fu, Jiyang; Huang, Yonhui
Abstract: In the engineering practice, arches, such as arch bridges, are often subjected to localized loading. It is known that the nonlinear in-plane instability of shallow arches is caused by the significant in-plane bending action. The different localized loading produces very different in-plane bending distributions and so the instability of arches under localized loading would be quite different from that under a central point load or under a radial load uniformly distributed over the entire arch. However, there are no studies about the nonlinear instability and post-instability of arches under localized loading reported in the literature. This paper presents nonlinear in-plane analyses for fixed shallow circular arches under a localized uniform radial load. Novel theoretical solutions for nonlinear equilibrium, limit point instability, and bifurcation instability for arches under a localized uniform load are obtained, and new theoretical solutions of the certain modified slenderness switching the instability patterns of an arch under localized uniform loading are also obtained. It is found that the length of localized loading segment significantly influences the in-plane instability and post-instability responses of an arch. The limit point and bifurcation instability loads decrease with a decrease of the length of the localized loading segment. However, the modified slenderness switching instability patterns is found to increase with a decrease of the length of the localized loading segment. Comparisons against the finite element results show the theoretical solutions derived in this paper are accurate. These theoretical solutions provide comprehensive solutions for nonlinear instability and post-instability of fixed arches and they can reduce to those under a central point load or to extend to those under a uniform load over the entire arch. Highlights: Novel theoretical solutions for nonlinear instability of arches under localized uniform loading. Localized loading influences nonlinear instability and post-instability of arches significantly. Decrease of length of loading segment leads to decrease of instability loads of arches. New theoretical solutions for criteria switching instability patterns of arches under localized uniform load. Decrease of length of loading segment leads to increase of modified slenderness switching instability patterns.